Colonoscopic features and malignant potential of sessile serrated adenomas: comparison with other serrated lesions and conventional adenomas. (2nd August 2016) - Kawasaki, K.; Kurahara, K.; Yanai, S.; Oshiro, Y.; Yao, T.; Kobayashi, H.; Nakamura, S.; Fuchigami, T.; Sugai, T.; Matsumoto, T.
Abstract: Aim: Sessile serrated adenomas/polyps (SSA/Ps) have been proposed as precursors of colorectal cancer. The aims of this investigation were to compare the endoscopic findings of SSA/Ps with those of other serrated lesions and to compare the histological findings of SSA/Ps with those of conventional adenomas. Method: We retrospectively reviewed colonoscopy records at our institution from 1984 to 2013 and identified cases of endoscopically or surgically resected conventional adenomas and serrated lesions, including SSA/Ps, hyperplastic polyps (HPs) and traditional serrated adenomas (TSAs). The colonoscopic findings of SSA/Ps were compared with those of the other two serrated lesions and histological findings were compared among all groups of lesions. Results: There were 79 HPs in 68 patients, 77 SSA/Ps in 63 patients, 167 TSAs in 145 patients and 6324 conventional adenomas in 4129 patients. The inverted type and flat‐elevated type were more frequent among SSA/Ps than among the other two types of serrated lesions. Magnifying colonoscopy revealed that a round and open pit pattern, expanded crypt openings and varicose microvascular vessels were more frequently observed among SSA/Ps than among the other types. The incidence of high‐grade dysplasia or carcinoma among SSA/Ps (13.0%) was significantly higher than that among HPs (0%, P < 0.001) and equivalent to that among conventional adenomas (12.3%). Conclusion: SSA/Ps have colonoscopic features distinct from those of HPs and TSAs. The malignant potential of SSA/Ps seems to be equal to that of conventional adenomas.